Experience in application Arbidol disease area rotavirus - V. V. Malyshev; A. V. Semena; V. S. Petukhov; I. O. Myasnikov (Журнал инфектологии, 2014)
Prevention of rotavirus infection in adults, especially in organized groups, remains an unresolved problem. That was the basis for use as a prophylactic agent in the organized collectives, where there is an emergence of rotavirus infection, an antiviral drug domestically Arbidol. In an open comparative study involved 500 men aged 18 to 22 years. Along with the general anti-epidemic measures for the prevention of acute intestinal infections in the experimental group (300 people) used Arbidol (0,2 g 1 per day for 10 days). Group comparisons were 200 people. The observation was carried out within 3 months after the prophylactic course. As a result, in the group treated Arbidol, the incidence of rotavirus infection was significantly lower (p <0,001) than in the comparison group. When comparing the data obtained for patients with acute intestinal unknown etiology indicates that in the experimental group the number of cases was significantly lower (p <0,001) than in controls. Thus, the use Arbidol in conjunction with organizational control measures can reduce the incidence of rotavirus infection.